La réception de la Première Guerre mondiale dans le champ culturel équatorien - Elodie Lenoël (Conserveries Mémorielles)
The First World War is an event with an unprecedented impact around the world. The centenary of its celebration is the opportunity to wonder about his real worldwide dimension. Here, the interest of paying attention to distant spaces, few studied until now but however relevant, as Ecuador. This country doesn't take part in fightings but has to position itself. Furthermore, the war economics consequences affected it a lot. The war impact is not limited to diplomatic and economic fields. The conflict is apparent in cultural life. It's omnipresent in the diaries but also in speeches and in ecuadorian cultural productions. Images spread, imaginaries set up. The distance with the conflict creates a specific observation prism. What kind of reception of the war can we observe ? What conflict's vision appear ? What evolutions in the way to see Europe war develops ?